Production stability of advanced rice lines long thin grain in Michoacán Mexico - Alvarez Hernandez, Juan Carlos; Tapia Vargas, Luis Mario; Hernández Pérez, Anselmo; Barrios Gomez, Edwin Javier; Pardo Melgarejo, Saul (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, long and thin rice is the most consumed, so its supply has depended mainly on imports. Consequently, the Mexican Rice Council handed INIFAP the elite lines that generated the Latin American Rice Irrigation Fund (FLAR) for the evaluation and selection of materials. In order to validate advanced lines of long and thin grain rice compared to conventional material under the conditions of the Michoacán production area, experimental works were developed in different cycles: autumn-winter 2014-2015 (trial 1), spring summer from years 2015 (trial 2), 2016 (trial 3) and 2017 (trial 4) and different genotypes: trial 1) INIFLAR RT, FL05601, “Milagro Filipino”; test 2) FL06747, FL08224, INIFLA R, INIFLAR RT, Ivory, Lombardy, “Milagro Filipino”; essay 3) Lombardy, FL08224, “Milagro Filipino”; and essay 4) Ivory, Lombardy “Milagro Filipino 2. The data recorded varied in each trial, but phenological and productive aspects were included, including yield. Analysis of variance and comparison of means were performed. In trial 1, treatments exceeded the regional average, between 8,000 and 8,500 kg ha-1. In trial 2, the treatments FL06747, INIFLAR R and Lombardy stood out significantly in performance. Also, the flowering and maturity of grain, appeared early compared to “Milagro Filipino”. In trials 3 and 4, the Lombardy treatment showed higher yields. It is concluded that the advanced lines presented capacity to adapt to the production area of Michoacán. These materials were superior to the conventional material, since they showed consistency in each trial.